2018
DOI: 10.17582/pujz/2018.33.1.42.46
|View full text |Cite
|
Sign up to set email alerts
|

Length Weight Relationship and Condition Factor of Guinean Tilapia Coptodon guineensis (Gunther, 1862) from the New Calabar River and Buguma Creek, Nigeria

Abstract: | This research was carried out to investigate the length-weight relationship and condition factor of Coptodon guineensis from the New Calabar River and Buguma Creek, Nigeria. Assessments of the length and weight parameters indicated that the total length ranged from 12.4 cm to 29.8 cm with a mean value of 17.84±0.40 and the weight varied between 41g to 640g in subject collected from New Calabar River population. In Buguma Creek, the total length ranged from 10.9 cm to 23.5 cm with a mean value of 14.99 ± 0.26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…This is because of high level of similarity due perhaps to the production of fertile hybrids from inter-specific spawning [15]. However, samples analyzed in this study present a range of metric and meristic characters which fits into some specific range reported for Oreochromis niloticus and Copton guineensis (16,17,18,19,20]. The present morphometric analysis of an 'ecotype' tilapia hybrid called 'Wesafu' and O. niloticus from Epe Lagoon and New Calabr Rivers, respctvely revealed high variability between the two and the morphometric measurements in Wesafu were not intermediate contrary to expectations.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This is because of high level of similarity due perhaps to the production of fertile hybrids from inter-specific spawning [15]. However, samples analyzed in this study present a range of metric and meristic characters which fits into some specific range reported for Oreochromis niloticus and Copton guineensis (16,17,18,19,20]. The present morphometric analysis of an 'ecotype' tilapia hybrid called 'Wesafu' and O. niloticus from Epe Lagoon and New Calabr Rivers, respctvely revealed high variability between the two and the morphometric measurements in Wesafu were not intermediate contrary to expectations.…”
Section: Discussionsupporting
confidence: 50%
“…The range, mean, standard error, median and mode of the meristic characteristics for the putative hybrid, Weasfu and O. niloticus are presented in Table2. In case of dorsal fin spines(14)(15)(16)(17), dorsal fin soft rays(12)(13)(14)(15)(16), pectoral fin soft rays(12)(13)(14)(15)(16), pelvic fin spines (1), and caudal fin rays(14)(15)(16)(17)(18)(19)(20)(21) in O. niloticus. The same measurements were recorded respectively as 16-18, 11-15, 12-15, 1 and 11-19 in the putative hybrid.…”
mentioning
confidence: 99%
“…As a result, size variation significantly affects fisheries knowledge and population trends (Alonso-Fernández et al 2021) and is among the most basic fisheries data metrics (Mehmood et al 2021). Hence, LWR offers helpful information about fish species in a specific geographic area (Olopade et al 2018). Although LWRs are similar among fish species, they may differ due to hereditary body form and physiological parameters and fluctuate seasonally (De Giosa et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The fish condition factor (K) acts as a physiological indicator of the well-being of the fish (Ajibare and Loto 2022). According to Olopade et al (2018), it assesses various biological and environmental parameters, including extent of fitness, gonad maturation, and appropriateness of environment concerning nutritional condition. It refers to the relative fatness of the individual fish, which represents stored energy.…”
Section: Introductionmentioning
confidence: 99%
“…omais is a common and important fish species in catches of fishermen in River Komadougou. Although there are several studies on LWR and condition factors of some fish species found in Nigeria water bodies (Eyo, 2003;Omoniyi and Agbon, 2008;Ndome and Eteng, 2010;Iyabo, 2015;Idowu et al 2017;Olopade et al, 2018), there exist scanty or no information on some aspect of biology (LWR and condition factors) of this fish species in River Komadougou, Northeast Nigeria. The wellbeing of this species is important for management and conservation strategies, policymakers, fish farmers and other fish-resource dependant (fishers' households).…”
Section: Introductionmentioning
confidence: 99%